2020
DOI: 10.1101/2020.04.25.043729
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pancreatic beta-cell specific deletion of VPS41 causes diabetes due to defects in insulin secretion

Abstract: Insulin secretory granules (SGs) mediate the regulated secretion of insulin, which is essential for glucose homeostasis. The basic machinery responsible for this regulated exocytosis consists of specific proteins present both at the plasma membrane and on insulin SGs. The protein composition of insulin SGs thus dictates their release properties, yet the mechanisms controlling insulin SG formation, which determines this molecular composition, remain poorly understood.VPS41, a component of the endo-lysosomal tet… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Interestingly, we found that expression of VPS41 S285P fully rescued the secretion defect in VPS41 KO PC12 cells. Likewise, in a parallel study we found that expression of VPS41 S285P in VPS41 KO INS-1 cells restored insulin secretion (Burns et al, 2020). This shows that expression of VPS41 S285P fails to restore HOPS function, but does rescue the regulated secretion pathway in PC12 and INS cells.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Interestingly, we found that expression of VPS41 S285P fully rescued the secretion defect in VPS41 KO PC12 cells. Likewise, in a parallel study we found that expression of VPS41 S285P in VPS41 KO INS-1 cells restored insulin secretion (Burns et al, 2020). This shows that expression of VPS41 S285P fails to restore HOPS function, but does rescue the regulated secretion pathway in PC12 and INS cells.…”
Section: Discussionmentioning
confidence: 51%
“…In secretory cells, VPS41 is required for secretory protein sorting and secretory granule biogenesis in a pathway that is independent of the HOPS complex (Asensio et al, 2013;Burns et al, 2020). This VPS41 function requires the N-terminal residues 1-36 for interaction with AP-3 and the presence of the C-terminal located CHCR domain (Asensio et al, 2013;Margarita Cabrera et al, 2010).…”
Section: Vps41 S285p Allows For Normal Regulated Secretion In Pc12 Cellsmentioning
confidence: 99%